Tuning the A-site cation composition of FA perovskites for efficient and stable NiO-based p–i–n perovskite solar cells. Issue 41 (9th October 2017) - Hu, Chen; Bai, Yang; Xiao, Shuang; Zhang, Teng; Meng, Xiangyue; Ng, Wai Kit; Yang, Yinglong; Wong, Kam Sing; Chen, Haining; Yang, Shihe
Abstract : Cation mixing has proved to be effective in stabilizing the high-temperature phase of formamidinium (FA)-based perovskites, affording high-performance n–i–p perovskite solar cells (PSCs). Abstract : Cation mixing has proved to be effective in stabilizing the high-temperature phase of formamidinium (FA)-based perovskites, affording high-performance n–i–p perovskite solar cells (PSCs). However, optimum cation mixing is found to be inapplicable directly to NiO p–i–n PSCs due to the energy band misalignment. In the present study, we reveal the role of mixing cesium (Cs), methylammonium (MA) and formamidinium (FA) in the energy band alignments and the crystallization of perovskites in such a device structure. By tuning the composition of mixed cations, we have significantly improved the energy band alignments of perovskites in p–i–n NiO-based PSCs. The relative amount of Cs to MA cations also plays a decisive role in shaping the nature of perovskite precursors, thus impacting the quality of the resulting perovskite layer in NiO p–i–n PSCs. These insights and the associated engineering efforts led to a significantly improved power conversion efficiency of 18.6% based on the NiO p–i–n PSCs, in addition to their superior ambient stability to typical n–i–p PSCs.